Self-medication practices in urban and rural areas of western India: a cross sectional study - Limaye, Dnyanesh; Limaye, Vaidehi; Fortwengel, Gerhard; Krause, Gerard (International Journal Of Community Medicine And Public Health, 2018)
Background: Concerns about practice of self-medication (SM) world across are based on associated risks such as adverse reactions, disease masking, increased morbidity, wastage of resources and antibiotic resistance. SM is likely to differ between rural and urban areas of India. Systematically retrieved evidence on these differences are required in order to design targeted measures for improvement. Methods: We conducted a cross sectional study among the general population in urban (Matunga) and rural (Tala) areas of Maharashtra, India to explore SM practices and its associated factors. Face to face interviews were conducted using the validated study questionnaire. Data was analyzed by using descriptive and analytical statistical methods. Results: A total of 1523 inhabitants from 462 households were interviewed between [June/2015] and [August /2015], 778 (51%) of them in rural and 745 (49%) in urban areas. Overall self-medication prevalence was 29.1% (urban; 51.5%, rural; 7.7%, OR 12.7, CI 9.4-17.2) in the study participants. Participants having chronic disease (OR: 3.15, CI: 2.07-4.79) and from urban areas (OR:15.38, CI:8.49-27.85) were more likely to self-medicate. Self-medication practices were characterized by having old prescription (41.6%) as the main reason, fever (39.4%) as top indication and NSAIDs (Non-Steroidal Anti Inflammatory Agents) as the most self-medicated category of drugs (40.7%). Conclusions: The present study documented that the prevalence of self-medication is associated with place of residence, and health status of the study participants. Self-medication is still a major issue in western Maharashtra, India and is majorly an urban phenomenon. Status of implementation of existing regulations should be reconsidered.